Resultados clínicos de serviço de gerenciamento da terapia medicamentosa na Atenção Primária à Saúde - Lívia Faria Gonçalves (2017)
The insertion of the comprehensive medication management (CMM) in Primary Health Care (PHC) is very rewarding, since it focuses on solving the drug related problems (DRPs), improving the patients health condition and avoiding predictable health problems, hence diminishing the public health care expenses. In such a way, the hereby-presented study aimed to evaluate the clinical results from a MTM service. The study regards all the patients accompanied by the MTM service in Lagoa Santas PHC (Minas Gerais) from October 2015 to February 2016. Clinical and social-demographic data were collected from the MTM patients medical records. At least two evaluations were carried out initial (descriptive data analysis) and secondary (services clinical results analysis). The clinical results were determined through calculations of DRPs index resolution rate and clinical-pharmacotherapy result rate. There were 342 medical records evaluated, but due to the limitation of not reported data in medical records, analyzes of clinical results of the service were possible for 174 patients. On the first evaluation, 460 DRPs were identified and 841 CPCs were classified. Out of all the DRPs identified, 35.7% were solved, while 0.9% were not, and for 63.5% there were no records regarding its resolution. The number of CPC on the secondary evaluation narrowed down to 448, where 348 held a positive result and 87 held a negative one. The DRPs index resolution rate obtained a result of 97.6%. For the positive clinical-pharmacotherapy result rate, the result was 77.7%, and for the negative clinical-pharmacotherapy result rate, the result was 19.4%. This study proved the MTM patients both social-demographic and clinical profiles to be very similar to other studies in the area (65.2% of the patients were women, mean age 59.9 years and average schooling of 5.4 years). The results obtained on this study proved that, despite the limitation due to incomplete medical records, this MTM service was satisfactory. Ultimately, this study evaluated the very first results from a newly implanted MTM service and showed the critical points necessary for its enhancement.